The Effect Of Social Capital And Organizational Commitment Toward Lecturer Performance With Islamic Work Ethics As A Moderating Role - Pardiman Pardiman (University of Islam Malang, 2018)
The number of private Islamic higher educations (PTIS) in Indonesia today amounted to 631 institutions. This condition has a tremendous potential in order to build the civilization of the Indonesian nation as aspired by Islam which is to be a nation that baldatun thoyyibatun wa rabbun ghaffur, a nation with a peace, the savety, and prosperity. The purpose of this study is to examine the impact of Islamic work ethic as moderating role on the influence of social capital and organizational commitment to the performance of lecturers. Researcher is using random sampling technique. The data collected from 236 respondents in PTIS that classified as “A” accredited by BANPT. Researcher analyzes the data collected by using WarlpPls 5.0. This research concluded that the social capital and organizational commitment has a positive effect on lecturer’s performance, Islamic work ethics reinforces these influences. However, the decision of researcher in choosing only “A” accredited as his research object make this study can’t be generalize.